Assessing the Threat of Indonesian ISIS Returnees: An Analysis of Ideological Mindsets and Operational Capabilities - Bimantara, Angga (Security Intelligence Terrorism Journal (SITJ), 2025)
The return of Indonesian citizens formerly associated with the Islamic State of Iraq and Syria (ISIS) as Foreign Terrorist Fighters (FTF) presents a complex challenge to national security. This research analyzes the threat posed by these returnees by focusing on their ideological radicalization and operational capacity. This study utilizes a qualitative methodology, drawing data from semi-structured interviews with returnees, counter-terrorism practitioners from BNPT, Densus 88, and BIN, and academic experts. The analysis is framed by two specific theories: Randy Borum’s "The Terrorist Mindset" to assess the stages of ideological development, and Kevin Riehle’s threat formula (Threat = Intent x Capability x Opportunity) to evaluate operational risk. The findings reveal a significant polarization in threat profiles. First, the "Combatant Profile" (including combat veterans and frustrated travelers) possesses high operational capabilities and knowledge and maintains latent ideological intent, driven by eschatological beliefs and network connections, posing a high-level, active threat. Second, the "Non-Combatant Profile" (including "civil society" members and dependents) demonstrates a near-total erosion of intent, driven by profound disillusionment with the reality of ISIS and traumatic experiences. While their ideological threat is low, they face significant socio-economic vulnerabilities. The study concludes that the threat from ISIS returnees is not monolithic and requires a bifurcated security response: prioritizing disengagement and surveillance for the high-risk combatant profile, while focusing on socio-economic integration for the low-risk, non-combatant profile to mitigate vulnerabilities.